3-E Analysis of a 3x500 MW coal fired thermal power plant using alternative coals species. Issue 1 (April 2021) - Rajeev, Vishnu; Sreekanth, M; Feroskhan, M; Daniel, Joseph
Abstract: This article reports a study conducted to understand the influence of different coal species on the performance of a thermal power plant. The aim is to understand the difficulties in replacing an existing coal with another available species. The methodology of 3-E (Energy, Exergy and Environment) analysis has been implemented on a 3x500 MW coal fired thermal power plant located in South India. The power plant is modelled using flow sheeting software called Cycle-Tempo. Key operating parameters like temperatures, mass flow rates were compared with the operating parameters and were found to be in good agreement. Maximum exergy loss for the design coal was found to occur in the combustor (36.5%), and the least exergy loss occurred in the de-aerator (0.13%). Optimization of the power plant was carried out with the aim of maximizing the efficiency, and the energy and exergy efficiencies obtained for the power plant were 34.35% and 33.64% respectively. Simulations were carried out with six different coal species, namely (i) Raniganj, (ii) Giridih, (iii) East Bokaro, (iv) West Bokaro, (v) Wardha valley, and (vi) Korba coals and various parameters that influence the performance were examined. An environment analysis was also carried out to study the emissions caused by the different species. East Bokaro coal turned out to be the best coal from efficiency viewpoint whereas Korba coal has the lowest amount of CO2 produced per MW power generated.